Life cycle cost optimisation in highway concrete bridges management - Almeida, Joana O. (2022)
This study presents a life cycle cost prediction and cost minimisation methodology for a set of highway concrete bridges, during a medium or a long period of time, in order to facilitate the decision process of the structure management. This methodology takes into consideration bridge intervention costs in addition with some Markov matrices degradation model. It applies a genetic algorithm in order to identify the optimised intervention plan, considering the available budget and the desired minimum performance level. Some Portuguese direct and indirect cost parameters, associated with different types of interventions during bridges lifetime, are presented. Finally, a probabilistic sensitivity analysis is carried out using Monte Carlo simulations.